2024
DOI: 10.1186/s12992-023-00987-w
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy and equity: lessons learned from the past and how they affect the COVID-19 countermeasure in Indonesia

Rano K. Sinuraya,
Rina F. Nuwarda,
Maarten J. Postma
et al.

Abstract: Introduction Indonesia has made progress in increasing vaccine coverage, but equitable access remains challenging, especially in remote areas. Despite including vaccines in the National Immunization Program (NIP), coverage has not met WHO and UNICEF targets, with childhood immunization decreasing during the COVID-19 pandemic. COVID-19 vaccination has also experienced hesitancy, slowing efforts to end the pandemic. Scope This article addresses the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This was also buttressed in a study where 92% of children of mothers with middle or higher education were fully immunized compared with 78% of children whose mothers had no education [ 60 ]. Maternal level of education plays a very important role as modifiers of vaccination experiences and behaviours, this helps to put at bay every myth and disbelief on malaria vaccinology [ 61 , 62 ]. An Indonesian study has shown that acceptance of vaccine was higher in individuals having postgraduate education compared with those with lower education level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also buttressed in a study where 92% of children of mothers with middle or higher education were fully immunized compared with 78% of children whose mothers had no education [ 60 ]. Maternal level of education plays a very important role as modifiers of vaccination experiences and behaviours, this helps to put at bay every myth and disbelief on malaria vaccinology [ 61 , 62 ]. An Indonesian study has shown that acceptance of vaccine was higher in individuals having postgraduate education compared with those with lower education level.…”
Section: Discussionmentioning
confidence: 99%
“…An Indonesian study has shown that acceptance of vaccine was higher in individuals having postgraduate education compared with those with lower education level. This high education levels among mothers with high vaccine acceptance has led to a very high improvement in acceptance and compliance [ 62 ]. The findings above were at variance with that seen in the Ethiopia where no association between caretakers’ educational level and vaccination was documented [ 63 ].…”
Section: Discussionmentioning
confidence: 99%